Bureaucratic Reform and Eradicating Corruption Crimes: Steps Towards a Healthy Economy - Putra, Zulfikar; Sopiandy, Dede; Umpi, Ridwan (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
The aim of this research is to optimize the role of bureaucratic reform which has an important role in preventing and eradicating corruption, with the aim of achieving a healthy economy. The research used is a qualitative normative legal approach with inductive logic, using comparative legal interpretation and construction tools. The results of this research are that the government, in this case, needs to optimize bureaucratic reform as a whole by simplifying procedures, increasing the professionalism of ASN and utilizing digital technology to speed up public services. Apart from that, bureaucratic reform is also needed to increase efficiency, improve public services, and create a conducive climate for investment and economic growth.